2014
DOI: 10.21307/sjcapp-2015-007
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Qualities of the Dimensional Assessment of Personality Pathology – Short Form for Adolescents

Abstract: Background: A growing body of research recognizes the occurrence and validity of personality pathology during adolescence as well as its relevance as a developmental precursor of adult personality pathology. Objective: The present study recognizes the need for a comprehensive and concise instrument to assess the dimensions of personality pathology in adolescents. Therefore, the psychometric qualities of an abbreviated version of the Dimensional Assessment of Personality Pathology -Basic Questionnaire for Adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…In a similar manner, they developed a short form containing 136 items for adolescents (DAPP-SF-A) from the DAPP-SF. The DAPP-BQ-A and DAPP-SF-A have been examined in the Netherlands, where adequate psychometric properties were established (20,21). These findings are in line with recent studies that provided evidence for the reliable measurement of PD in adolescents using the PID-5 model (22)(23)(24).…”
Section: Introductionsupporting
confidence: 74%
“…In a similar manner, they developed a short form containing 136 items for adolescents (DAPP-SF-A) from the DAPP-SF. The DAPP-BQ-A and DAPP-SF-A have been examined in the Netherlands, where adequate psychometric properties were established (20,21). These findings are in line with recent studies that provided evidence for the reliable measurement of PD in adolescents using the PID-5 model (22)(23)(24).…”
Section: Introductionsupporting
confidence: 74%
“…The lower-order dimensions are enlisted in Table 3 except for Intimacy problems. The internal consistency of the lower-order dimensions was found to be good and the dimensions showed adequate discriminant validity all indicating large effects in the distinction between subsamples of adolescents referred for clinical intervention regarding DSM-IV-TR (APA, 2000) Axis I disorders, Axis II disorders, and between the referred and a community sample (Tromp & Koot, 2015). The internal consistency reliability of intimacy problems is reported to be low in adolescent samples (Tromp & Koot, 2008).…”
Section: Methodsmentioning
confidence: 94%
“…The relative lack of experience of adolescents in these domains might have affected the assessment of intimacy problems. Psychometric analyses have furthermore shown that the intimacy problems scale had low test–retest reliability and poor accuracy (Tromp & Koot, 2012). Future research should examine DP in relation to these aspects of personality pathology in an adult sample and perhaps with different measures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, children with dysregulation were found to be more harm avoidant, which contains elements of shyness and reluctance to engage with peers (Althoff et al, 2012). Generally, parent–adolescent agreement is low on the less visible internalizing behaviors such as withdrawn behavior (Rescorla et al, 2014; Rubin, Althoff, Walkup, & Hudziak, 2013), and intimacy problems (Tromp & Koot, 2012), and therefore detachment features should also be examined using adolescent self-report.…”
Section: Predictive Validity Of the Dp For Personality Pathologymentioning
confidence: 99%